Inotuzumab ozogamicin and blinatumomab sequential therapy for relapsed/refractory Philadelphia chromosome-positive acute lymphoblastic leukemia. (2022) - Ueda, Tomoaki; Fukushima, Kentaro; Kusakabe, Shinsuke; Yoshida, Koki; Suga, Makiko; Nakai, Ritsuko; Koike, Midori; Hino, Akihisa; Akuta, Keigo; Toda, Jun; Nagate, Yasuhiro; Doi, Yukiko; et al.
Highlights: The outcome of R/R Ph+ALL is dismal. Single cycle of Inotuzumab ozogamicin could achieve CR without VOD/SOS. Blinatumomab could achieve and keep MRD negativity without CRS. InO-Blina is effective and safe for R/R Ph+ALL as a bridging regimen before allo-SCT. Abstract: To overcome the unfavorable outcome of refractory/relapsed (R/R) Philadelphia chromosome-positive acute lymphoblastic leukemia (Ph+ALL) and conduct allogeneic stem cell transplantation (allo-SCT) safely, we designed a sequential therapy involving a single cycle of Inotuzumab ozogamicin (InO) and Blinatumomab (Blina). Two heavily treated and aged patients with R/R Ph+ALL were treated with the therapy. Both of them achieved complete molecular remission without cytokine release syndrome and underwent allo-SCT without veno-occlusive disease/sinusoidal obstruction syndrome. Although appropriate central nervous system prophylaxis should be added, the InO-Blina sequential therapy is a promising strategy for treating R/R Ph+ALL as a bridging regimen before allo-SCT.